2019
DOI: 10.3390/ijms20205094
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Dynamin Gene Family in cassava (Manihot esculenta Crantz) and Transcriptional Regulation of Family Members ARC5 in Hormonal Treatments

Abstract: The Dynamin gene family play a significance role in many physiological processes, especially ARC5 (Accumulation and replication of chloroplasts 5) in the process of plastid division. We performed a genome-wide analysis of the cassava Dynamin family based on the published cassava genome sequence and identified ARC5. 23 cassava Dynamins (MeDynamins) were identified and renamed. 23 MeDynamins were further divided into five major groups based on their structural and phylogenetic characteristics. The segmental dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Domain loss appears to be common in monocots such as rice and maize, and the loss of the WRKY domain is among the divergent forces of WRKY gene family expansion [35][36][37]. In C. pepo, the C-terminal of Group I CpWKRY55 lacked a conserved heptapeptide sequence, and the CpWRKY39 C-terminal demonstrated the loss of the zinc finger structure.…”
Section: Discussionmentioning
confidence: 99%
“…Domain loss appears to be common in monocots such as rice and maize, and the loss of the WRKY domain is among the divergent forces of WRKY gene family expansion [35][36][37]. In C. pepo, the C-terminal of Group I CpWKRY55 lacked a conserved heptapeptide sequence, and the CpWRKY39 C-terminal demonstrated the loss of the zinc finger structure.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have mined and identified many functional genes by constructing a co-expression regulatory network [ 31 , 84 , 85 ]. Additionally, among the 43 candidate genes, DAO , which encodes a growth-hormone-oxidizing dioxygenase, was able to rapidly respond to nitrogen stress [ 86 ]; OsSultr1;1, the sulfate transporter protein, was regulated by nitrogen in a previous study [ 87 ]; Os08g0533300 was presumed to be ACR5 (accumulation and replication of chloroplasts 5), which has been significantly and positively correlated with plant growth [ 88 ]; and OsWNK6 may be functionally similar to OsWNK9 , which negatively regulated root elongation [ 89 , 90 ]. These results suggest that these 43 candidate genes may participate in the regulation of the nitrogen uptake and utilization in rice and improve the adaptability of rice to low-nitrogen conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ]. Spraying exogenous hormones can significantly affect the growth and development of cassava; for instance, a high concentration of MeJA could induce the cassava defense mechanism to play a role in advance [ 41 , 42 , 43 ]. The application of auxin can stimulate the growth of cassava stem and bud, and tubulins play an important role in this process [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%